In vitro micropropagation of Jasminum grandiflorum L. - Rahman, Md S; Mouri, NJ; Nandi, NC; Akter, S; Khan, Md S (Bangladesh Journal of Scientific and Industrial Research, 2018)
An efficient protocol was developed for in vitro plant regeneration of Jasminum grandiflorum L. The highest elongated shoots (60%) were achieved from axillary meristems using MS (Murashige and Skoog ) basal medium supplemented with 1 mg/l 6-benzyladenine (BAP) and 60 mg/l coconut water. After adding 1.0 mg/l BAP and 45 mg/l coconut water in the culture medium, the highest rate of shoot proliferation was exhibited after 4 weeks of culture. Rooting was found within 14-23 days after the cut end of shoots was soaked in 1.5 mg/l IBA solution for 3-7 minutes. The regenerated healthy rooted plantlets were transferred to small plastic pot containing garden soil and compost in a ratio of 2:1. Maximum (75%) in vitro rooted plants were survived in the shade house and finally survived naturally in soil condition. The successful protocol for in vitro regeneration was developed which will facilitate the conservation and propagation of the important medicinal plant. Bangladesh J. Sci. Ind. Res.53(4), 277-282, 2018